Different Relevance of Peripheral, Central or Nighttime Blood Pressure Measurements in the Prediction of Chronic Kidney Disease Progression in Patients with Mild or No-Proteinuria - Piotr Kuczera; Katarzyna Kwiecień; Marcin Adamczak; Teresa Bączkowska; Jolanta Gozdowska; Katarzyna Madziarska; Hanna Augustyniak-Bartosik; Marian Klinger; Magdalena Durlik; Eberhard Ritz; Andrzej Wiecek (Karger Publishers, 2018)
Background/Aims: Arterial hypertension is one of the leading factors aggravating the course of chronic kidney disease (CKD). It seems that the novel parameters used in the assessment of the blood pressure (BP) load (i.e. central blood pressure, nighttime blood pressure) may be more precise in predicting the cardiovascular risk and the progression of CKD in comparison with the traditional peripheral blood pressure measurements in the office conditions. The aim of the study was to assess the impact of the central, or nighttime blood pressure on the progression of CKD in patients with mild or no-proteinuria (autosomal, dominant polycystic kidney disease or IgA nephropathy). Methods: In each of the enrolled 46 patients with CKD stage 3 or 4, serum creatinine concentration was assessed, eGFR (MDRD) was calculated, also central blood pressure and pulse wave velocity (PWV) was assessed and the 24-hour ambulatory blood pressure monitoring (ABPM) was conducted at the beginning of the study and then repeated after one-year observation period. Results: During the observation period mean eGFR decreased from 44.1 (33.2-50.6) mL/min to 36.7 (29.7-46.3) mL/min. No significant differences were observed in the peripheral blood pressure or central blood pressure parameters. After one-year observation period the values of diastolic blood pressure dipping during the night significantly decreased from 16 (13-19) mmHg to 12 (10-15) mmHg; p< 0.05. The values of systolic dipping during the night or the mean BP values recorded in ABPM did not change significantly. Additionally, no significant differences in the PWV values were found. In the multivariate regression model the change of serum creatinine concentration was explained by the initial diastolic dipping values. Conclusion: 1. In patients with CKD stages 3 or 4 and mild or no- proteinuria, peripheral and central blood pressure did not change significantly during a one-year observation period despite the significant decline of eGFR and seems not to participate in the CKD progression. 2. Reduced magnitude of the diastolic dipping, which reflects the increase of diastolic blood pressure load during the nighttime, may play an important role in the pathogenesis of deterioration of kidney function in these patients.